PENGARUH PEMBERIAN BUAH PEPAYA (Carica papaya L.) TERHADAP KADAR KOLESTEROL LDL DAN KOLESTEROL HDL PADA TIKUS SPRAGUE DAWLEY DENGAN HIPERKOLESTEROLEMIA - Asmariani, Widitha Gustining; Probosari, Enny (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Increased LDL cholesterol concentrations and low plasma HDL cholesterol concentrations are well-established risk factors for cardiovascular disease. Diet modification is one of recommended theraphy to decrease LDL cholesterol level by increasing fiber intake from fruit. Papaya contains niacin, fiber, and antioxidant which can decrease LDL cholesterol level. It also contains quercetin to increase HDL cholesterol level. The aim of this study was to prove the effect of papaya of different dosages on LDL and HDL cholesterol of hypercholesterolemic rats. Methods: This research was true-experimental using pre-post test with control group design. Subjects were male Sprague Dowley rats, 7-8 weeks old, 100-200 grams weight, inducted hypercholesterolemia, given papaya diet using 5,4 gr, 7,2 gr, and 9,0 gr dosage for 4 weeks. LDL cholesterol and HDL cholesterol were measured by direct method using LDL-C Select (DiaSys) reagent and CHOP-PAP methods respectively. Normality of the data was tested by Shapiro Wilks test. Data were analyzed by paired t test continued with One Way Anova.and post-hoc LSD. Result: The study revealed that papaya of dosage 5,4 gr/day decreased LDL cholesterol (p<0,05) significantly from 45,29±9,05 mg/dl to 30,29±5,31 mg/dl but nonsignificantly decrease HDL cholesterol level (p=0,930) from 25,71 ± 5,09 to 25,57 ± 3,59 mg/dl at the same dosage. Other dosage of 7,2 mg/day and 9,0 gr/day neither significantly decrease LDL cholesterol level nor increase HDL cholesterol level. Conclusion: Papaya couldn’t decreased LDL cholesterol and increased HDL cholesterol in hypercholesterolemic rats.